Farmer perspectives on desired catfish attributes in aquaculture systems in Nigeria. An exploratory focus group study - Manyise, Timothy; Komugisha, Basiita Rose; Mwema, Catherine; Oyesola, Olutokunbo; Siriwardena, Sunil; Fregene, Bernadette; Cole, Steven; Brako Dompreh, Eric; Dam Lam, Rodolfo; Lozano, Denise; Rossignoli, Cristiano; Benzie, John (Elsevier, 2024)
As a first step to determine the focus of potential genetic improvement programs for African catfish in Nigeria, we conducted a study to identify the preferred attributes among catfish producers across three states renowned for aquaculture production, in December 2022. Employing a qualitative approach, data were collected through 11 focus group discussions involving 123 participants. The findings indicate that farmers prioritize a range of catfish attributes related to both consumption and production. The top five production-related attributes identified by farmers include stress tolerance, disease resistance, fast growth, robustness, and high survival rates. For consumption-related attributes, preferences were for large, long, heavy catfish, with abundant flesh and thickness. Notably, the prioritization of these attributes varied among catfish farmers both between and within states, reflecting diverse farming objectives and market dynamics. Future research is essential to define precise objectives and scope for selective breeding program design, considering the investment necessary for the success of such programs and how they can accommodate the diverse preferences identified.